Influence of preparation parameters on rheological properties and relation analysis of waste rubber modified bitumen mastic - Zhang, Honggang; Zhang, Yangpeng; Chen, Jie; Liu, Wenchang; Wang, Wensheng (Frontiers in Materials, 2024)
Waste rubber modified bitumen has gained significant attention as a sustainable and innovative material in the field of pavement engineering. This study aims to evaluate the performance of rubber modified bitumen mastic by considering its rheological properties, specifically focusing on preparation parameters, i.e., rubber content, mesh number, and filler to bitumen ratio. From the experimental results, the rheological properties of rubber modified bitumen mastic were significantly influenced by preparation parameters. Increasing the rubber powder content in bitumen mastic results in higher viscosity. Increasing the rubber content improves high-temperature rutting resistance to a certain extent, however, excessive rubber powder content would result in weakened high-temperature performance improvement. The rutting factor decreases gradually with an increase in the rubber mesh number. A ratio of filler to bitumen of 0.95 exhibits the best resistance to rutting at high temperatures. Higher rubber content and larger mesh number correspond to stronger low-temperature crack resistance in bitumen mastic. As the ratio of filler to bitumen increases, the low-temperature deformation capacity gradually decreases, resulting in weaker low-temperature crack resistance. Based on the grey relation analysis, the ratio of filler to bitumen has the greatest impact on the high and low-temperature rheological properties of bitumen mastic, followed by the rubber content. The rubber mesh number has a relatively lower impact. It is crucial to control the ratio of filler to bitumen to avoid excessive values. When possible, a higher rubber powder content should be used while meeting process requirements. These findings provide valuable insights into the design and optimization of rubber modified bitumen mastic, which can contribute to the development of sustainable and high-performance bitumen mixtures, promoting the use of recycled rubber in pavement engineering.